Isolation of antimicrobial compounds from aniseed and techno‐economic feasibility report for industrial‐scale application. (19th May 2022) - Bontzolis, Christos; Plioni, Iris; Dimitrellou, Dimitra; Boura, Konstantina; Kanellaki, Maria; Nigam, Poonam S.; Koutinas, Athanasios
Summary: This work evaluates the antimicrobial activity of the fractionated aqueous extract obtained from the aerial parts of aniseed. Fifteen fractions were collected by column chromatography using ethanol and water as mobile phases. All fractions were tested as potential antimicrobial agents against three common food‐spoilage microorganisms: a yeast ( Saccharomyces cerevisiae ), a mold ( Aspergillus awamori ) and a bacterium ( Lactobacillus delbrueckii subsp. bulgaricus ). Fraction 2 exhibited the highest antimicrobial activity in both types of susceptibility test, and therefore, it was further studied for the identification of bioactive compounds. GC‐MS analysis of Fraction 2 revealed the presence of threo‐Anethole glycol. Based on laboratory‐scale experiments, a process flowsheet for potential industrial‐scale application is proposed combined with a techno‐economic feasibility report. Fraction 2 with the detected compound threo‐Anethole glycol showed promising results encouraging the attempts for industrial‐scale application of antimicrobial compounds produced from aniseed. Abstract : The isolation of antimicrobial compound(s) from aniseed extracts applying column chromatography is presented. Silica gel was used as packing material while ethanol and water were used as mobile phase for the elution of fractions. The extraction of aniseed carried out with hot water and the extract was fractionated in the chromatographic column. The antimicrobial activity of the fractions has been examined against food spoilage microbes ( Saccharomyces cerevisiae, Lactobacillus bulgaricus and Aspergillus awamori ). Fractions with positive antimicrobial activity were identified by GC‐MS analysis.